The Role of Special Education Centers in Meeting the Social Needs of Autistic Children Parents from Their Perspective - atif Khalaf Al-Ramamneh, AbdelL; Abdelkarim Sabayleh, Obaid (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to assess the extent to which the emotional social needs of the parents of children with autism spectrum disorder (ASD) in Jordan’s special education centers are met from their perspective. The researcher used a quantitative research method and an interview as a study tool. The study sample consisted of (50) parents of ASD children who were interviewed in Amman, Zarqa, Balqa, Karak, and Tafilah. Data analysis was performed using descriptive analysis. The results indicated that the families of autistic children in Jordan are not satisfied with the services provided by the employees who worked in special education centers in meeting their social and emotional needs. The results also show that there is a positive participation from the parents and the special education centers in providing care and education to the ASD children. The results show that there is also a gap in providing medical services for ASD parents. This study gained the confidence of ASD parents in Jordan and not only validated the existing findings but also offered insights and important information in providing them with knowledge in this specific area.